2019
DOI: 10.1155/2019/7463412
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Nutrient Intake and Malnutrition as Predictors of Uremic Oxidative Toxicity in Patients with End-Stage Renal Disease

Abstract: Oxidative stress is an important risk factor for cardiovascular disease and death in hemodialysis (HD) patients. However, whether biochemical and nutritional markers might be useful to stratify HD patients according to the risk of oxidative damage remains unclear. We investigated whether low-cost and easily available parameters such as the profile of nutrients intake, nutritional status, and antioxidant defenses can predict lipid and protein oxidation in HD patients. Forty-nine HD patients (women = 20, men = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…This situation is dangerous as the production of toxins can lead to a high mortality rate in these patients as their renal function is already compromised. 22,23 When it comes to the anthropometric variables, we had a mean BMI of 27.6 ± 5.1 kg/m 2 , Triceps skin fold thickness was 18.2 ± 7.1 mm and a mean mid upper arm circumference of 23.2 ± 3.9 mm 2 , which is similar to other similar studies. 20 In the modification in the diet in renal disease (MDRD) studies, the benefits of a low protein diet were assessed in patients with CKD.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This situation is dangerous as the production of toxins can lead to a high mortality rate in these patients as their renal function is already compromised. 22,23 When it comes to the anthropometric variables, we had a mean BMI of 27.6 ± 5.1 kg/m 2 , Triceps skin fold thickness was 18.2 ± 7.1 mm and a mean mid upper arm circumference of 23.2 ± 3.9 mm 2 , which is similar to other similar studies. 20 In the modification in the diet in renal disease (MDRD) studies, the benefits of a low protein diet were assessed in patients with CKD.…”
Section: Discussionsupporting
confidence: 83%
“…57.3% of the patients were being seen by a nephrologist for great then1 year, 31.4% were under the care for less than six months, and 14.1% were in care for less than one month. 22 In our study, we used the body mass index as a tool to determine malnutrition. The mean body mass index was found to be 45.65 ± 1.94 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Silva et al (2019) found no difference in markers of oxidative stress and antioxidant defenses in malnourished HD patients identified using global objective assessment compared to mild or well-nourished patients [ 95 ]. In contrast, accumulation of advanced glycation end products, a biomarker of oxidative stress measured using skin auto fluorescence, was significantly associated with markers of malnutrition in HD patients such as lower serum albumin, lower handgrip strength, and lower protein intake [ 96 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…Concerning patients undergoing HD, Silva et al [ 15 ] found no statistically significant associations between nutritional status and OS status in HD patients while Epifano et al [ 16 ] found inverse associations between nutrient intake with antioxidant properties (Cu, Zn, Mn, vitamin C and ω-3, vitamin E) and plasma nitric oxide (NO) concentrations in HD patients.…”
Section: Resultsmentioning
confidence: 99%